The Influence of Extracorporeal Membrane Oxygenation on Antibiotic Pharmacokinetics - Gregory J. Peitz; Daryl J. Murry (MDPI AG, 2023)
Extracorporeal membrane oxygenation (ECMO) is becoming increasingly utilized to support critically ill patients who experience life-threatening cardiac or pulmonary compromise. The provision of this intervention poses challenges related to its complications and the optimization of medication therapy. ECMO's mechanical circulatory support is facilitated via various devices and equipment that have been shown to sequester lipophilic- and protein-bound medications, including anti-infectives. Since infectious outcomes are dependent on achieving specific anti-infectives' pharmacodynamic targets, the understanding of these medications' pharmacokinetic parameters in the setting of ECMO is important to clinicians. This narrative, non-systematic review evaluated the findings of the most recent and robust pharmacokinetic analyses for commonly utilized anti-infectives in the setting of ECMO. The data from available literature indicates that anti-infective pharmacokinetic parameters are similar to those observed in other non-ECMO critically ill populations, but considerable variability in the findings was observed between patients, thus prompting further evaluation of therapeutic drug monitoring in this complex population.